Early surgical intervention for extensive nontuberculous mycobacterial pulmonary disease - T.-F. Kuo; M.-R. Lee; H.-L. Huang; K.-C. Chen; M.-W. Lin; S.-W. Kuo; P.-M. Huang; H.-H. Chen; J.-Y. Wang; J.-S. Chen (IJTLD Open)
BACKGROUND: Adjuvant lung resection surgery benefits selected patients with nontuberculous mycobacterial pulmonary disease (NTM-PD); however, optimal timing remains controversial. This study evaluated surgical outcomes and prognostic factors, with a focus on the timing of surgical intervention. METHODS: This study included 41 patients with NTM-PD who underwent adjuvant lung resection surgery between January 2000 and August 2022. Data on patient characteristics, surgical procedures and postoperative outcomes were analyzed. The primary outcome, defined as freedom from unfavorable outcomes (mortality, failure to achieve sputum culture conversion, or microbiological recurrence), was estimated using the Kaplan–Meier method, with prognostic factors analyzed by Cox regression model. RESULTS: Extensive disease was observed in 35 (85%) patients. The median preoperative antibiotic duration was 3.2 months. Twenty-two (54%) patients received lobectomies, whereas 15 (37%) received wedge resections. Thirty-four (83%) achieved sputum culture conversion. The probability of being free from unfavorable outcomes within two years was 80%. Independent favorable prognostic factors included body mass index ≥ 18.5 kg/m2 (p=0.007) and early surgical intervention (preoperative antibiotic duration < 3 months, p=0.039). Additionally, early surgical intervention correlated with shorter operation time (p=0.03). CONCLUSIONS: Early surgical intervention, irrespective of the surgical approach, appeared feasible and potentially beneficial even in patients with extensive NTM-PD.